The motor unit number index (MUNIX) profile of patients with adult spinal muscular atrophy. Issue 11 (November 2018) - Querin, Giorgia; Lenglet, Timothée; Debs, Rabab; Stojkovic, Tanya; Behin, Anthony; Salachas, François; Le Forestier, Nadine; Amador, Maria del Mar; Lacomblez, Lucette; Meininger, Vincent; Bruneteau, Gaelle; Laforêt, Pascal; et al.
Highlights: MUNIX values are decreased in type III and IV spinal muscular atrophy (SMA) patients compared to healthy controls. The MUNIX profile of SMA patients correlates with muscle strength and disability. The MUSIX values of SMA patients are increased and Suggesting active re-innervation. Abstract: Objective: Objective of this study is the comprehensive characterisation of motor unit (MU) loss in type III and IV Spinal Muscular Atrophy (SMA) using motor unit number index (MUNIX), and evaluation of compensatory mechanisms based on MU size indices (MUSIX). Methods: Nineteen type III and IV SMA patients and 16 gender- and age-matched healthy controls were recruited. Neuromuscular performance was evaluated by muscle strength testing and functional scales. Compound motor action potential (CMAP), MUNIX and MUSIX were studied in the abductor pollicis brevis (APB), abductor digiti minimi (ADM), deltoid, tibialis anterior and trapezius muscles. A composite MUNIX score was also calculated. Results: SMA patients exhibited significantly reduced MUNIX values ( p  < 0.05) in all muscles, while MUSIX was increased, suggesting active re-innervation. Significant correlations were identified between MUNIX/MUSIX and muscle strength. Similarly, composite MUNIX scores correlated with disability scores. Interestingly, in SMA patients MUNIX was much lower in the ADM than in the ABP, a pattern which is distinctly different from that observed in Amyotrophic Lateral Sclerosis. Conclusions: MUNIX is a sensitive measure of MU loss in adult forms of SMA and correlates with disability. Significance: MUNIX evaluation is a promising candidate biomarker for longitudinal studies and pharmacological trials in adult SMA patients.